Analysis of Cotton Yarn Product Defects in the Production Process of the Cotton Department Using the DMAIC Six Sigma Approach - Adinda Herliani Dewi; Asep Hermawan; Hady Sofyan (BRIDGE : The Multidisciplinary Research Portal, 2024)
The smoothness of the production process is an indicator of success in increasing the effectiveness of a manufacturing industrial company. In the product manufacturing process, several types of defects occur , such as dirty thread, uneven thread rolls, tangled threads or non-standard loose thread rolls and others. This research focuses on finding types, defect factors , sigma values and RPN at PT. Indorama Teknologies Complex uses the DMAIC and FMEA Phase approach methods . In this research, researchers collected data by means of observation and interviews. Observations were carried out by direct observation at the research site taking place at PT . Indorama Teknologies Complex . Interviews were conducted with a question-and-answer session regarding the possible causes of product defects with production operators and supervisors in the field . The average sigma value of the yarn production process cotton is 4.19 sigma. because there was a value that exceeded the control limit, a revision was carried out which made the sigma value increase to 4.22. The sigma value is still at level 4. Based on the 5W+1H analysis, the proposed improvement is strict supervision so that maintenance on the machine is carried out according to the schedule set by the company on a regular basis.